Attitudes and Expectations of Health Sciences Students Towards Artificial Intelligence‏ in Medical Education and Professional Communication - Tabishat, Mohammed; Hafiz, Abdu Dawood (Journal of Ecohumanism, 2025)
The transition of healthcare systems towards digitalization, particularly through the integration of artificial intelligence (AI), is reshaping medical practice and education. AI’s role in enhancing diagnosis, patient care, and distance education is becoming increasingly significant, prompting a need for strategic planning, investment, and training in the healthcare workforce. This study focuses on the attitudes of health science students at the University of Fujairah towards AI in medical services, particularly in developing countries where AI can address personnel shortages. A literature review reveals that while health science students globally exhibit positive attitudes towards AI, gaps in knowledge and skills persist, necessitating improved educational programs. The study employs a quantitative methodology, utilizing a standardized questionnaire to assess students’ perceptions of AI’s impact on healthcare efficiency, patient engagement, and ethical concerns. The sample comprises 92 students, ensuring representation across various academic disciplines. Findings indicate a duality in students’ perspectives: while there is enthusiasm for AI’s transformative potential, concerns about data privacy and the erosion of personal interactions in patient care are prevalent. Gender differences emerge, with male students showing higher trust in AI, while female students express greater apprehension regarding data security. As students progress in their studies, they become more critical of AI’s impact on personal interactions, highlighting the need for educational programs to address these concerns. In conclusion, the study underscores the importance of integrating AI education into healthcare curricula, focusing on data privacy and patient-centered approaches. Recommendations include enhancing early-year educational modules on AI and conducting further research to understand the evolving perceptions of students towards AI in healthcare. This research provides a foundation for developing strategies that ensure the effective integration of AI while maintaining the essential human touch in patient care.